The Application of Diorama Media on Eclipse Material to Enhance Science Learning Interest in Sixth Grade Elementary School Students - Sairendri, Ni Wayan; Numertayasa, I Wayan; Darmayanti, Ni Wayan Sri (The Future of Education Journal, 2025)
This research aims to enhance the learning interest of sixth-grade elementary school students in science, specifically on the topic of eclipses, through the application of diorama media. Conducted as Classroom Action Research (CAR) at SD Negeri 1 Sulahan with 18 students, the study implemented a two-cycle approach involving planning, execution, observation, and reflection. Data was collected through tests, questionnaires, observations, and interviews. The findings revealed a significant increase in student interest and learning outcomes after utilizing diorama media. Initially, only 31.2% of students achieved mastery in the pre-cycle stage, which rose to 56.26% in Cycle I and further to 87.5% in Cycle II. This indicates that diorama media effectively facilitates understanding of abstract concepts like eclipses, fostering greater engagement and comprehension among students.